Profiling Oncogenic Germline Mutations in Unselected Chinese Lung Cancer Patients - Yang, Jie; Li, Hefei; Li, Ben; Li, Wei; Guo, Qiang; Hu, Ling; Song, Zizheng; Zhou, Bin (Frontiers in Oncology, 2021)
Introduction: Emerging evidence has suggested that inherited factors are involved in lung cancer development. However, most studies focused on well- elucidated cancer predisposition genes, the majority of which are tumor suppressor genes. The germline mutation profile in oncogenic driver genes remains unrevealed, which might also provide potential clinical implications for lung cancer management. Methods: Sequencing data from 36,813 unselected lung cancer patients who underwent somatic mutation profiling were retrospectively reviewed. All recruited patients had matched white blood cell samples sequenced in parallel using a capture-based panel including 8 key lung cancer driver genes (epidermal growth factor receptor (EGFR), anaplastic lymphoma kinase (ALK), MET proto-oncogene, receptor tyrosine kinase (MET), Kirsten rat sarcoma viral oncogene homolog (KRAS), Erb-B2 receptor tyrosine kinase 2( ERBB2), ROS proto-oncogene 1, receptor tyrosine kinase (ROS1), ret proto-oncogene (RET), and B-Raf proto-oncogene, serine/threonine kinase (BRAF)). Likely pathogenic/ pathogenic (LP/P) variants were called according to the classification criteria of the American College of Medical Genetics and Genomics (ACMG). Variants of uncertain significance (VUS) located in the kinase domains of driver genes and occurring recurrently (n≥3) were also included for further analyses. Results: Seven different LP/P variants in EGFR, MET, or RET were identified in 0.03% of lung cancer patients (n=14) and 25 different VUS in the kinase domains of 7 driver genes (except KRAS) were found with a prevalence of 0.3% (n=117).Collectively, germline mutations were most frequently seen in ROS1 (n=31, 0.084%), followed by MET (n=23, 0.062%), EGFR (n=22, 0.06%), ALK (n=22, 0.06%) and RET (n=17, 0.046%). LP/P variants and VUS fell the most commonly in EGFR (n=10, 72%) and ROS1 (n=31, 26%), respectively. Of the 10 patients with EGFR LP/P germline mutation, 70% also acquired somatic EGFR driver mutation exon21 p.L858R or exon19 deletion at baseline; while the 3 patients with pathogenic germline RET mutation displayed distinct baseline somatic profiles of rare EGFR mutation or KRAS exon2 p.G12C. We discovered 11 germline mutations that also occurred somatically, including 4 LP/P variants and 7 VUS. Conclusion: We present the first study to systemically characterize the germline mutation in driver genes in a large cohort of unselected lung cancer patients.